Estudio de prefactibilidad para la instalación de una planta productora de bebidas energizantes a partir de açaí (euterpe oleracea) - Ledesma Lapeyre, Adriana Teresa (2023)
This prefactibility work seeks to determine the market, technical and economic-financial viability for the installation of an energy drinks production plant based on açaí, which are presented in a 250 ml aluminum can and have the mission of achieving the maximum potential of the consumer. In the first chapter, the preliminary research was developed and the objectives and hypotheses that lead to the viability of the project were established. In the second chapter, the market study was carried out, where, based on different segmentation criteria, the project demand was determined, which reached 475 899 units of açaí-based energy drinks in the last year of operation. In the third chapter, relevant macro and micro location factors were evaluated for an effective location selection, therefore, the Ventanilla district in the city of Lima was chosen for the implementation of the Açaí Boost plant. Then, the plant size was defined based on the project demand, which was 475 899 cans of energy drinks; likewise, the equilibrium point was 27 425 cans. In the fifth engineering chapter of the project, the technical specifications and characteristics of the product, the production process and the resources required for development were analyzed. Likewise, key factors and other calculations were analyzed that made it possible to establish the layout of the 820.74 m2. plant. Later, in chapter six the mission and vision of the company were defined; as well as the functions and requirements of the staff, which are 7 of administrative staff and 15 of production. In relation to the seventh chapter, it was determined that the total investment would be S/ 1 850 757; Based on this, the principal economic and financial indicators were calculated, such as the NPV of S/. 164 672 and S/. 367 788 with an IRR of 14% and 19% respectively; In addition, the payback period and the benefit-cost demonstrated the profitability of the project. In chapter eight, the social impact was evaluated based on indicators such as the density and intensity of capital, which resulted in S/. 84 125 and 29% respectively. Finally, the conclusions and recommendations of the research work were drawn up.